Phenomenological Study on Employee Experience of Work-Life Imbalance and Burnout at PT NT Indonesia - Sintiya Mariani (PT ARFA DIGITAL TECHNOLOGY, 2025)
The phenomenon of work-life imbalance and burnout is a real problem in the modern work environment, especially in the manufacturing sector with a dense work system and high production targets. This study aims to deeply understand the experiences of PT NT Indonesia employees in dealing with the imbalance between work and personal life and its impact on their psychological condition. The approach used is qualitative with a phenomenological method, through in-depth interviews with employees who have worked for at least two years. The results of the study show that work-life imbalance is experienced due to long working hours, frequent overtime, and high production demands. Employees feel like they're losing time for family and personal lives, and experience repetitive physical and emotional burnout. Burnout appears in the form of extreme fatigue, loss of work morale, and the desire to resign. However, employees still try to survive with simple strategies such as taking a break on the weekends, enjoying entertainment, or enjoying time with family. These findings show that burnout is not only an individual problem, but also related to the company's work structure and policies. Therefore, attention and managerial policies that are more in favor of employee welfare are needed to create a healthy balance between work and personal life.